Organic template-free synthesis of high-quality CHA type zeolite membranes for carbon dioxide separation ' - Jang, Eunhee; Hong, Sungwon; Kim, Eunjoo; Choi, Nakwon; Cho, Sung June; Choi, Jungkyu (ELSEVIER SCIENCE BV, 2018)
Microporous chabazite (CHA) zeolite is very promising for CO2 capture because of its appropriate pores with molecular dimensions for the preferential adsorption of CO2 molecules. Herein, CHA type zeolite particles and membranes were prepared by using a seeded growth method in the absence of an organic structure directing agent (OSDA) or template. After substantial effort to find appropriate and reliable conditions for obtaining continuous CHA type zeolite membranes, it was recognized that the formation of these membranes is a highly sensitive function of the Si/Al ratio in the synthetic precursor. Using the appropriate Si/Al ratio of similar to 50, OSDA-free CHA type zeolite membranes were manufactured with high reproducibility. The resulting OSDA-free CHA type zeolite membranes showed maximum CO2/N-2 and CO2/CH4 separation factors of similar to 12.5 +/- 3.8 and similar to 28.8 +/- 6.9, respectively, with a moderate CO2 permeance of similar to 1 x 10(-7) mol m(-2) s(-1) Pa-1. Notably, under more realistic wet conditions (i.e., in the presence of H2O vapor), the separation performance at temperatures above 75 degrees C was comparable to that obtained under dry conditions, although permeation was hindered below 50 degrees C, apparently due to the strong adsorption of H2O vapor.
Keywords: ACID-WATER MIXTURES; PERMEATION PROPERTIES; SECONDARY GROWTH; ZSM-5 MEMBRANES; MFI MEMBRANES; PERVAPORATION SEPARATION; SAPO-34 MEMBRANE; SSZ-13; CHABAZITE; CAPTURE